Support for Requirement Traceability: The Tropos Case - Pinto, Rosa Candida; Silva, Carla; Castro, Jaelson (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2005)
For many years, the research and business communities have agreed that the traceability is very important in the software development process. It helps the impact analysis of required changes, improving the efficient management of software projects and hopefully improving the software quality. Software development methodologies supporting requirement traceability can develop and maintain higher quality software with less cost. Our research aims to support traceability through the agent-oriented software lifecycle. In particular, this paper proposes a requirement traceability process to be used in the requirements specifications and system architecture models of the Tropos framework. An e-commerce example is used to demonstrate the applicability of the proposed approach.